‘Quantum Mechanics’ and ‘Scientific Explanation’ An Explanatory Strategy Aiming at Providing ‘Understanding’ - Hadzidaki, Pandora (Science & education, 2008)
Empirical studies persistently indicate that the usual explanatory strategies used in quantum mechanics (QM) instruction fail, in general, to yield understanding. In this study, we propose an instructional intervention, which: (a) incorporates into its subject matter a critical comparison of QM scientific content with the fundamental epistemological and ontological commitments of the prominent philosophical theories of explanation, a weak form of which we meet in QM teaching; (b) illuminates the reasons of their failure in the quantum domain; and (c) implements an explanatory strategy highly inspired by the epistemological pathways through which, during the birth-process of QM, science has gradually reached understanding. This strategy, an inherent element of which is the meta-cognitive and meta-scientific thinking, aims at leading learners not only to an essential understanding of QM worldview, but to a deep insight into the ‘Nature of Science’ as well.